A qualitative investigation of meta-imagery processes and imagery direction among elite athletes - MacIntyre, T. E.; Moran, A. P. (Journal of Imagery Research in Sport and Physical Activity, 2007)
It has long been known that athletes use mental imagery extensively for a variety of different purposes. Although many of these purposes have been well documented, several gaps remain in our understanding of atheletes' imagery experiences. First, the issue of negative or debilitative imagery among athletes has received little research attention in sports psychology. In addition, until recently, athletes' meta-imagery processes (i.e., their beliefs about the nature and regulation of their own imagery skills) have been neglected. So, the purpose of the present study is to use qualitative methodology to explore meta-imagery processes and imagery direction (i.e., facilitative or debilitative) in elite sports performers. The sample comprised seven participants from motor-sport, rugby, fencing and golf (mean age = 24.43 years; SD = 1.99). Results showed that motivational aspects of imagery were not as relevant to our sample of elite performers as they appear to have been in previous studies using non-elite samples. In addition, the elite performers in our study showed evidence of sophisticated meta-imagery control skills - being able, for example, to restructure negative imagery so that it facilitates future performance. Finally, our elite sample's experience of imagery direction seems to be more complex than had previously been believed. For example, some athletes reported deliberately imagining errors in order to prepare for "worst-case" scenarios in competition (hence using such imagery to facilitate their performance). Overall, we propose that existing imagery use taxonomies that need to be revised to take into account the flexibility with which elite athletes actually employ imagery.